Fertility Differences Between Migrants and Stayers in a Polygamous Context: Evidence from Senegal - Elisabeth K. Kraus; Amparo González-Ferrer (Journal of International Migration and Integration, 2021)
This study takes a 'country-of-origin' or dissimilation perspective to compare the timing of births and completed fertility of international migrants and of those who stay at origin. In order to disentangle selection effects determining differential fertility behaviour of migrants, other mechanisms explaining migrant fertility (disruption, interrelation of events) are also examined. Furthermore, we take into consideration the prevalence of polygamy in Senegal to enhance our knowledge of migrant fertility in this specific context. For the empirical analysis, we use longitudinal data collected in the framework of the MAFE-Senegal project (Migrations between Africa and Europe), which includes retrospective life histories of non-migrants in Senegal and migrants in France, Italy and Spain. We estimate discrete time hazard models and Poisson regressions for male and female respondents separately to analyse the timing of first and higher-order births as well as completed fertility. The results show a strong disruptive effect of migration on childbearing probabilities for men and women, clearly related to the geographic separation of partners due to the out-migration of the man. Increased birth risks in the first year upon arrival could be observed for migrant women following their husbands to Europe, suggesting an interrelation of migration and fertility events. Regarding completed fertility, migrants have significantly fewer children by the age of 40 compared to their non-migrant counterparts, which among men is largely driven by a strong negative effect of polygamous migrants.
Keywords: 300; Migration; Fertility; Polygamy; Sub-Saharan Africa; MAFE